Unravelling the link between circadian clock genes and brain tumors: From pathological disruptions to potential therapeutic interventions - Albaqami, Amirah (Frontiers in Pharmacology, 2025)
The circadian clock is present in nearly all tissues (including glial cells), which play crucial roles in brain functions and development. Circadian clock genes (CCGs) are responsible for regulating numerous cancer-associated biological mechanisms, including the regulation of cell cycle genes, apoptosis, and cell proliferation. A range of studies have already confirmed the potential link between brain tumors and CCGs, including Bmal1, Clock, Period 1, Period 2, Period 3, Cry1, Cry2, retinoid-related orphan receptor-α (ROR-α). Growing evidence regarding gliomas including glioblastoma multiforme (GBM) indicates the significance of modulation of CCG in cancer biology. Various studies have already revealed how tumor cells can disrupt CCGs to safeguard their survival. It has also recently been demonstrated in the case of gliomas (especially GBM) that CCGs should be targeted for the development of novel therapies or to ameliorate the current treatments that impair and abolish tumor growth. Multiple pharmacological modulators have been reported as effective in regulating CCGs in brain tumors, such as temozolomide, inhibitors of casein kinase 1 and casein kinase 2, curcumin, norepinephrine, melatonin, REV-ERB agonists, agonists of the retinoic acid-related orphan receptor, cryptochrome protein stabilizers, and 1A-116. In this review, an overview of brain tumors, the genetics of circadian clock, and the link between pathological disruptions of the CCGs and brain tumor development have been discussed. In addition, potential pharmacological interventions to modulate CCGs in brain tumors have also been reviewed.